Ochrana nezletilých dětí jako součást sociální politiky - Závurka, Milan (Univerzita Pardubice, 2007)
Inseparable part of the social policy is indisputably minor children protection. For number of years in common matters operate without problems especially the particular children care departments of municipal and local offices. However problems with providing this care detected in connection with so called international children abduction. The question is whether this special sphere should be provide by one special body with the whole country competence or by particulat departments of local administratice bodys. Legislator is trying to solve this question but nevertheless it is still matter for futher discussion.
Keywords: minor children protection; particular children care departments; international children aduction